New equations for age estimation using four permanent mandibular teeth in Thai children and adolescents - P. Duangto (2018)
© 2018 Springer-Verlag GmbH Germany, part of Springer Nature The purposes of this study were to generate new age estimation equations using two four-teeth methods and to test the accuracy of the resulting equations in comparison with Demirjian and Goldstein four-teeth methods in a Thai population. A sample of 720 digital panoramic radiographs of Thai individuals (360 males and 360 females), aged between 7 and 15 years was randomly selected and assessed for age estimation. The new equations were developed using quadratic regression analysis. The results showed the Thai population-specific equations had a strong relationship between the dental maturity score and the chronological age in both sexes (r = 0.946–0.956). The new equations revealed no statistically significant differences between the estimated and the chronological ages in either sex. On the other hand, Demirjian and Goldstein four-teeth methods showed statistically significant differences between the estimated and the chronological ages in both sexes. Moreover, we found slight differences in the mean absolute error between Demirjian and Goldstein methods and our new equations (0.01 years for males and 0.03 years for females in method I and 0.04 years for males and 0.02 years for females in method II) and the root mean square error between Demirjian and Goldstein methods and our new equations (0.02 years for males and 0.04 years for females in method I and 0.00 years for males and 0.04 years for females in method II). In summary, although Thai population-specific equations provide a slightly increased accuracy in age estimation in Thai children and adolescents, Demirjian and Goldstein methods are still relevant.